[PP.06.13] ANXIETY AS A PERSONALITY TRAIT CORRELATES WITH SHORT-TERM SYSTOLIC BLOOD PRESSURE VARIABILITY. (September 2017) - Symonides, B.; Wolynczyk-Gmaj, D.; Fornal-Pawlowska, M.; Splocharski, G.; Gaciong, Z.; Wojnar, M.
Abstract : Objective: Systolic blood pressure variability (SBPV) was found to increase cardiovascular risk independent of basal BP values. We studied the relationship between anxiety, which is one of risk factors for hypertension, and short-term SBPV in a group of subjects referred for 24-hr ambulatory BP monitoring (ABPM) because of "labile" hypertension. Design and method: Nineteen subjects without any concomitant diseases and not taking any centrally acting drugs (9/10 males/females, age 52.9 ± 15.8 yrs., range: 23–76) were examined. Their office SBP and daytime SBP were 138 ± 10 mm Hg (range: 116–155 mmHg) and 126 ± 12 mmHg (range: 105–153 mm Hg), respectively. Anxiety was measured as a current symptom and a personality trait using State-Trait Anxiety Inventory (STAI). Short-term BPV was calculated as a standard deviation (SD) and coefficient of variance (CV) of systolic BP (SBP). Results: SBPV expressed as SD was 14.4 ± 3.7 mmHg (range: 9.0–24.4 mmHg), 12.8 ± 3.7 mmHg (range: 8.6–23.7 mmHg) and 11.4 ± 3.0 mm Hg (range: 7.8–18.0 mmHg) and expressed as CV was 12 ± 11% (range: 8–22%), 10 ± 3% (range: 7–19%), 10 ± 3% (range: 7–14%) for daily, daytime and nighttime measurements, respectively. On the STAI-trait and STAI-state subscales the average scores were, respectively, 43.2 ± 9.4 (range: 22–60) and 37.1 ± 10.6 (range: 25–62). There was no correlation between daily, daytime and nighttime SBP and STAI scores on both subscales. However, STAI-trait correlated significantly with SBP daytime SBPV - SD (r = 0.56, p = 0.013) and CV (r = 0.58, p = 0.0086) and STAI-state with office SBP (r = 0.49, p = 0.0218) and CV of daytime SBPV (r = 0.46, p = 0.0498). Conclusions: In a small group of subjects, anxiety assessed as a personality trait correlated with daytime variability of SBP. Further studies are needed to evaluate relationship between anxiety and cardiovascular risk related to BP variability.